Characteristics of Chronic Kidney Disease Patients Undergoing Hemodialysis at RSPAL Dr. Ramelan Surabaya from January to June 2022 - Carolina, Anita; Wibowo, Prajogo; Prameswari, Renata (Universitas Nahdlatul Ulama Surabaya, 2024)
Chronic Kidney Disease (CKD) is a persistent abnormality in kidney function or structure, with or without a decline in glomerular filtration rate (GFR) below 60 mL/min/1.73 m², lasting for more than three months. CKD diagnosis relies on markers of kidney damage and/or a reduction in GFR. Patients with advanced CKD, characterized by a GFR below 15 mL/min/1.73 m², typically require dialysis. In 2018, 60,852 individuals in Indonesia were reported to have CKD requiring lifelong dialysis. This study aims to assess the characteristics of CKD patients undergoing hemodialysis. This research employs descriptive design. The sample consists of all CKD patients undergoing hemodialysis, as recorded in the medical records of RSPAL dr. Ramelan Surabaya between January and June 2022. The findings reveal that more than half of the patients (52.7%) had been on hemodialysis for more than 12 months. Many of the patients (66.2%) were between 40 and 60 years old, with males accounting for 54.1% of the sample. Hypertension and diabetes mellitus were identified as the most common comorbid conditions (31.1%), while pain medication consumption was the least reported cause (2.7%). All patients had hemoglobin levels below the normal range (<13 g/dL for males and <12 g/dL for females) and relied on BPJS (Indonesia’s national health insurance) to cover the cost of hemodialysis. Furthermore, most patients exhibited creatinine levels exceeding 1.5 mg/dL, blood urea nitrogen (BUN) levels above 24 mg/dL, serum iron (SI) levels between 45 and 158 µg/dL, and total iron-binding capacity (TIBC) levels below 250 µg/dL.